2018
DOI: 10.1017/ice.2018.55
|View full text |Cite
|
Sign up to set email alerts
|

Urine Culture on Admission Impacts Antibiotic Use and Length of Stay: A Retrospective Cohort Study

Abstract: OBJECTIVETo examine the impact of urine culture testing on day 1 of admission on inpatient antibiotic use and hospital length of stay (LOS).DESIGNWe performed a retrospective cohort study using a national dataset from 2009 to 2014.SETTINGThe study used data from 230 hospitals in the United States.PARTICIPANTSAdmissions for adults 18 years and older were included in this study. Hospitalizations were matched with coarsened exact matching by facility, patient age, gender, Medicare severity-diagnosis related group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…In addition to our study finding no clinical benefit, antibiotic treatment of ASB was associated with a 37% increase in duration of hospitalization after urine testing, suggesting potential harm and additional cost. Similarly, a recent study found that hospitalized patients with a UC on admission, irrespective of their admitting diagnosis, had longer hospital stays compared with patients with no UC . The association of antibiotic treatment with longer duration of hospitalization was robust in sensitivity analyses attempting to account for differences in patients with testing performed later during hospitalization.…”
Section: Discussionmentioning
confidence: 87%
“…In addition to our study finding no clinical benefit, antibiotic treatment of ASB was associated with a 37% increase in duration of hospitalization after urine testing, suggesting potential harm and additional cost. Similarly, a recent study found that hospitalized patients with a UC on admission, irrespective of their admitting diagnosis, had longer hospital stays compared with patients with no UC . The association of antibiotic treatment with longer duration of hospitalization was robust in sensitivity analyses attempting to account for differences in patients with testing performed later during hospitalization.…”
Section: Discussionmentioning
confidence: 87%
“…The hospitals contributing to this database are generally representative of hospitals across the United States, except that there are fewer small facilities (i.e., Ͻ50 beds) and fewer facilities in the western United States; these differences were Յ5% from the national averages determined by the American Hospital Association. We have used this database for prior studies of antibiotic use (43,46).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the hierarchical nature of the data, we used multilevel logistic regression to analyze the predictive value of various admission characteristics on FQ use in both the AAD group and the Marfan syndrome group. We have used this approach in prior studies to examine the effects of urine culture at admission on antibiotic selection (46). The levels were facilities and attending physicians, which means we accounted for clustering of observations by facility and attending level.…”
Section: Methodsmentioning
confidence: 99%
“…A urine culture is often the first step in a chain of events leading to unnecessary antibiotic use, longer hospital stays, and other harms. 8 , 9 , 10 , 11 Therefore, investigators including members of our team 12 designed an intervention that focuses on reducing both unnecessary urine cultures (diagnostic stewardship) and unnecessary antibiotic use (antibiotic stewardship). This intervention package, the Kicking CAUTI (catheter-associated urinary tract infection) Campaign, consists of a validated guideline-based algorithm plus individualized audit and feedback.…”
Section: Introductionmentioning
confidence: 99%
“…A urine culture is often the first step in a chain of events leading to unnecessary antibiotic use, longer hospital stays, and other harms . Therefore, investigators including members of our team designed an intervention that focuses on reducing both unnecessary urine cultures (diagnostic stewardship) and unnecessary antibiotic use (antibiotic stewardship).…”
Section: Introductionmentioning
confidence: 99%